2020
DOI: 10.1097/scs.0000000000006956
|View full text |Cite
|
Sign up to set email alerts
|

Traction Applying Technique on Bicanalicular Crawford Silicone Tube to Overcome the Notching Deformity After Lacrimal Canalicular Repair

Abstract: Lower eyelid avulsion injury with lower canalicular laceration generally occur just medial to the punctum with insufficient skin remnant for repair causing tension on repair margins. The inevitable blinking force, along with the tension widens the repair margin, resulting in an aesthetically challenging notch at the medial lower lid. The authors attempted to minimize this notching deformity with a traction applying technique on bicanalicular silicone tube. Fifteen patients were enrolled and divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…In addition, the incidence of complications was considerably lower in the observation group (13%) than in the control group (28%) ( P < 0.05), indicating that reasonable and effective pouch surgery can alleviate the occurrence of complications after surgical treatment and improve the safety of surgery. This was consistent with a number of clinical research results, and the symptomatic degree of surgical method has a certain impact on the outcome of surgical treatment and the occurrence of postoperative complications [ 27 29 ]. Therefore, accurate examination and surgical method design is the pursuit of various clinical surgical treatment and is also very important to improve patient satisfaction, especially in the cosmetic and plastic surgery industry.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the incidence of complications was considerably lower in the observation group (13%) than in the control group (28%) ( P < 0.05), indicating that reasonable and effective pouch surgery can alleviate the occurrence of complications after surgical treatment and improve the safety of surgery. This was consistent with a number of clinical research results, and the symptomatic degree of surgical method has a certain impact on the outcome of surgical treatment and the occurrence of postoperative complications [ 27 29 ]. Therefore, accurate examination and surgical method design is the pursuit of various clinical surgical treatment and is also very important to improve patient satisfaction, especially in the cosmetic and plastic surgery industry.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the incidence of complications was considerably lower in the observation group (13%) than in the control group (28%) (P < 0:05), indicating that reasonable and effective pouch surgery can alleviate the occurrence of complications after surgical treatment and improve the safety of surgery. This was consistent with a number of clinical research results, and the symptomatic degree of surgical method has a certain impact on the outcome of surgical treatment and the occurrence of postoperative complications [27][28][29]. Therefore, accurate examination and surgical method design is the pursuit of various clinical surgical treatment and is also very important to improve indicates that the pouch degree, lower eyelid skin wrinkles, and skin gloss score of patients in the two groups were significantly improved compared with those before operation (P < 0:05); "#" indicates that the pouch degree, lower eyelid skin wrinkles, and skin gloss score of patients in the observation group were better improved after treatment compared with those in the control group (P < 0:05).…”
Section: Mildsupporting
confidence: 91%
“…Stents are most commonly removed after 3 months, although this may be safely extended to a period of 4 to 6 months depending on the extent of the trauma and subsequent repair. 11,13,24 Crawford stents may be removed from within the nares with cooperation from the patient if the stent can be located and cut above the knot. If the stent cannot be visualized endonasally, it may also be removed from the puncta.…”
Section: Canalicular Injuriesmentioning
confidence: 99%
“…Indirect injuries are also more commonly associated with extensive injuries elsewhere in the orbit. Although these etiologies vary significantly depending on geographic location and acute care setting, indirect injuries appear to be more common, 13,24,25 although one large retrospective review also found that direct injuries occur with comparable frequency. 26 When there is a suspicion for canalicular injury, it is important to identify any canalicular dehiscence precisely for repair (►Figs.…”
Section: Canalicular Injuriesmentioning
confidence: 99%
See 1 more Smart Citation